Mouse telomerase reverse transcriptase (mTert) expression marks slowly cycling intestinal stem cells - Montgomery, Robert K. (National Academy of Sciences, 2011)
The intestinal epithelium is maintained by a population of rapidly cycling (Lgr5(+)) intestinal stem cells (ISCs). It has been postulated, however, that slowly cycling ISCs must also be present in the intestine to protect the genome from accumulating deleterious mutations and to allow for a response to tissue injury. Here, we identify a subpopulation of slowly cycling ISCs marked by mouse telomerase reverse transcriptase (mTert) expression that can give rise to Lgr5(+) cells. mTert-expressing cells distribute in a pattern along the crypt–villus axis similar to long-term label-retaining cells (LRCs) and are resistant to tissue injury. Lineage-tracing studies demonstrate that mTert(+) cells give rise to all differentiated intestinal cell types, persist long term, and contribute to the regenerative response following injury. Consistent with other highly regenerative tissues, our results demonstrate that a slowly cycling stem cell population exists within the intestine.